2006
DOI: 10.4018/jgim.2006010103
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Development Lenses to Understand E-Government Development

Abstract: As governments at different levels and all around the world are increasingly using the Web to enhance and improve their services, understanding e-government development and exploring factors that affect e-government development have become important research topics. The purpose of this research is to investigate factors explaining e-government development in terms of social development lenses. Based on growth and regional development theories, the paper hypothesizes that income level, development status, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 15 publications
6
72
0
2
Order By: Relevance
“…Consequently, previous studies that have analyzed the influence of economic wealth (e.g., Christiaens, 1999;Laswad et al, 2005;Siau and Long, 2006;Kim, 2007;Tolbert et al, 2008;Serrano-Cinca et al, 2009) have usually found a positive association between the level of wealth and the use of e-government.…”
Section: Wealth or Economic Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, previous studies that have analyzed the influence of economic wealth (e.g., Christiaens, 1999;Laswad et al, 2005;Siau and Long, 2006;Kim, 2007;Tolbert et al, 2008;Serrano-Cinca et al, 2009) have usually found a positive association between the level of wealth and the use of e-government.…”
Section: Wealth or Economic Developmentmentioning
confidence: 99%
“…Therefore, e-government is currently considered to be not only a tool for reporting but also an effective communication channel for citizens to participate in democratic institutions and political processes (Justice et al, 2006;Siau and Long, 2006). In this way, the image of the public administration can be improved; citizens can perceive governments as accessible, transparent, responsible, effective and participatory as they increasingly use public websites to communicate and to conduct procedures and complete paperwork with them (Tolbert and Mossberger, 2006).…”
Section: The Evolution Of E-governmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 1990s, public-sector organizations across the globe have been applying internet technology and other computing technologies in innovative ways to deliver services, engage citizens, and improve efficiency using a set of practices commonly known as electronic government (e-government) [1]. E-Government is rapidly becoming one of the government's critical means for the provision of seamless services for public agencies, businesses, and citizens [2,3]. It is the use of information and communication technologies as a tool to achieve better government.…”
Section: Introductionmentioning
confidence: 99%